PKU dietary handbook to accompany PKU guidelines - MacDonald, Anita; Wegberg, Anna van; Ahring, K.; Beblo, S.; Belanger-Quintana, A.; Burlina, Angelo; Campistol, Josep M.; Mehdorn, Türkan; Feillet, F.; Giżewska, Maria; Huijbregts, S. C.; Leuzzi, Vincenzo; et al. (Orphanet journal of rare diseases, 2020)
Background Phenylketonuria (PKU) is an autosomal recessive inborn error of phenylalanine metabolism caused by deficiency in the enzyme phenylalanine hydroxylase that converts phenylalanine into tyrosine. Main body In 2017 the first European PKU Guidelines were published. These guidelines contained evidence based and/or expert opinion recommendations regarding diagnosis, treatment and care for patients with PKU of all ages. This manuscript is a supplement containing the practical application of the dietary treatment. Conclusion This handbook can support dietitians, nutritionists and physicians in starting, adjusting and maintaining dietary treatment.